Advances in the diagnosis and management of small bowel neuroendocrine tumours - Nezhentsev, Andrey; Soonawalla, Zahir (Journal of the Nuffield Department of Surgical Sciences, 2022)
Small bowel neuroendocrine tumours (SBNETs) are neoplasms arising from the neuroendocrine cells of the small intestine. SBNETs are the most common tumours of the small bowel. Their often unspecific symptoms mean that many patients present late with metastatic disease, most commonly to local lymph nodes, small bowel mesentery, and the liver. Although Somatostatin Analogues (SSAs) can relieve symptoms and slow disease progression, surgical resection remains the only curative option. In this case report, a patient undergoes surgical resection of her primary SBNET and several liver metastases. During the operation it becomes apparent that much of the metastatic liver spread is unresectable, and the aim of the surgery becomes tumour de-bulking. This report reveals the limitations of current SBNET imaging, biomarkers and surgical techniques, and explores recent advances.